(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Worldwide prostate cancer is the second most frequent cause of cancer deaths. Screening techniques isuseful for improving survival rates and treatment outcomes can be employed to detect the disease earlier inapparently healthy individuals, and increasing evidence shows that this can decrease morbidity and mortalityof the disease.Objectives: The objectives of this study was to assess the knowledge concerning contributing factors andearly detection to screen for prostate cancer among male staff of the University of Baghdad Colleges in babAlmudam Area, Iraq and to find out the relationship between employees’ knowledge and their demographicalcharacteristic.Methodology: This cross-sectional descriptive design study was carried out with 100 male staff workingin colleges of Baghdad University in bab-Almudam region. Male staff who agreed to participate and wererecruited on giving oral consent. Knowledge about prostate cancer and screening was operationalizedthrough 28items, including 12 items from the Knowledge about Prostate Cancer Screening Questionnaire,and 16 items assessing contributing factors and prostate cancer screening controversy. Data was collected bydistributing structured a self-administered questionnaire, written in Arabic was used.Results: The Majority of participants (36.0%) were ages between (38 -47) years, the median age was 36years (range, 18-36) years (mean=41.8+ S.td =10.035). Regarding marital status, the majority (77 %) wasmarried, followed by (19%) who were single and (4%) who were divorced or widowed. One third (38%) ofparticipants had PhD education, following by (26%) secondary school, (18 %) university,(9%) intermediate,)5%) MSc and (4%) institute education. Furthermore, (89%) of study participants reported they had nofamily history of prostate only (11%) reported had family history PCa. A total of (94%) were living in urbanarea and reminder lived in rural area. About (48%, 35%) respectively, of respondents had a medium and highknowledge level about prostate cancer and early detection screening methods.Conclusions: This study indicated that the staffs of University of Baghdad Colleges have appreciableknowledge regard contributing factors and early detection to prostate cancer screening. A significantproportion of staff however, exhibited poor knowledge of prostate cancer screening and contributing factorsto prostate cancer.